The methane-oxidizing microbial communities of three maar lakes in tropical monsoon Asia - Bicaldo, Iona Eunice C.; Padilla, Karol Sophia Agape R.; Tu, Tzu-Hsuan; Chen, Wan Ting; Mendoza-Pascual, Milette U.; Vicera, Carmela Vannette B.; de Leon, Justine R.; Poblete, Kamille N.; Austria, Eleanor S.; Lopez, Mark Louie D.; Kobayashi, Yuki; Shiah, Fuh-Kwo; et al. (Frontiers in Microbiology, 2024)
Methane-oxidizing bacteria (MOB) is a group of planktonic microorganisms that use methane as their primary source of cellular energy. For tropical lakes in monsoon Asia, there is currently a knowledge gap on MOB community diversity and the factors influencing their abundance.Herewith, we present a preliminary assessment of the MOB communities in three maar lakes in tropical monsoon Asia using Catalyzed Reporter Deposition, Fluorescence In-Situ Hybridization (CARD-FISH), 16S rRNA amplicon sequencing, and pmoA gene sequencing. Correlation analysis between MOB abundances and lakes' physicochemical parameters following seasonal monsoon events were performed to explain observed spatial and temporal patterns in MOB diversity. The CARD-FISH analyses detected the three MOB types (I, II, and NC10) which aligned with the results from 16S rRNA amplicons and pmoA gene sequencing. Among community members based on 16S rRNA genes, Proteobacterial Type I MOB (e.g., Methylococcaceae and Methylomonadaceae), Proteobacterial Type II (Methylocystaceae), Verrucomicrobial (Methylacidiphilaceae), Methylomirabilota/NC10 (Methylomirabilaceae), and archaeal ANME-1a were found to be the dominant methane-oxidizers in three maar lakes.Analysis of microbial diversity and distribution revealed that the community compositions in Lake Yambo vary with the seasons and are more distinct during the stratified period.Temperature, DO, and pH were significantly and inversely linked with type I MOB and Methylomirabilota during stratification. Only MOB type I was influenced by monsoon changes. This research sought to establish a baseline for the diversity and ecology of planktonic MOB in tropical monsoon Asia to better comprehend their contribution to the CH4 cycle in tropical freshwater ecosystems.